Жизненный цикл проекта лизинга морского судна судовладельца и фрахтователя - Бондарь, А. В. (НТУ "ХПИ", 2016)
На основании изученных видов бербоут-чартера, как формы лизинга на морском транспорте, построены алгоритмы принятия решений по обоснованию соответствующих проектов. Описаны жизненные циклы проектов финансового лизинга морского судна с позиции лиссора-судовладельца и рентера-фрахтователя. Выделены основные фазы жизненного цикла, что позволяет определить продукты проектов и их ценность на каждой фазе.

Based on the study of the basic types of the bareboat charter, presented algorithms decision on the justification of the respective projects. It was found that the initiator of the project can be both owner who wants to pass the boat rental and the charterer, and also who is the owner, who wants to take a boat for rent. It is proved that the implementation of these specific operations requires careful preparation, and using of the project approach will greatly enhance their effectiveness. We describe the life of the project finance lease from the standpoint of the marine vessel, the ship-owner and charterer. It is established that such projects characterized by four-phase structure of the life cycle: preparation, let's call it as the principal decision on (from) the chartering of the vessel, the investment - to select the optimal variant (from) the charter and the conclusion of the bareboat charter, the phase of operation of the vessel and the fourth - the closure of the project at the end of term bareboat charter. Skill description of the content of each phase, which will continue for the main participants of the project to determine the value of each phase and the value of the whole project.
Project Life Cycle leasing marine vessel owners and charterers
Keywords: лизинговый проект; лиссор-судовладелец; рентер-фрахтователь; бербоут-чартер; life cycle; project leasing; lеssor-owner; renter-charterer; bareboat charter